Muslim Community Dramaturgy Through Ritual Cross-Religious in Moluccas, Indonesia - Ridwan, M.; Sulaeman, Sulaeman; Hadawiah, Hadawiah; Darma, Darma; Tetulau, Muhammad (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2024)
On December 2, 2018, Immanuel Church of GPM Amahusu Klasis in Moluccas, Indonesia, hosted a cross-religious ritual involving the Muslim and Christian communities. The